Health or harm? A cohort study of the importance of job quality in extended workforce participation by older adults - Jennifer Welsh; Lyndall Strazdins; Sara Charlesworth; Carol T. Kulik; Peter Butterworth (BMC, 2016)
Abstract Background As people are living longer, they are being encouraged to work longer. While it is assumed that extended employment will be good for health, the evidence has been mixed. This study considers whether employment and job quality exert an influence on four indicators of health status in older workers. Methods Data for this study came from 836 older workers (440 men and 396 women) aged 50-59 years at baseline who participated in the Household, Income and Labour Dynamics in Australia (HILDA) Survey. Using linear regression, we examine within-person change in self-rated, physical and mental health and one health behaviour (physical activity) at two time points over a nine year follow-up period. Results There were minimal differences in the way health changed for older adults who continued working compared to those who retired voluntarily. However, when we decomposed employment in terms of job quality, health outcomes diverged. Compared to voluntary retirees, older workers who had worked in good quality jobs reported marginally better self-rated health (0.14,−0.02-0.29); but did not differ in their physical (2.31,−1.09-5.72) or mental health (0.51,−1.84-2.87). In contrast, older workers who held poor quality jobs for most of the follow-up period declined in their self-rated (−1.13,−0.28 − -0.02), physical (−4.90, 8.52- − 1.29) and mental health (−4.67, 7.69- − 1.66) relative to voluntary retirees. Older workers who held poor quality jobs for just some of the follow-up period did not differ from voluntary retirees in terms of their health. However there was evidence of a linear relationship between length of exposure to poor quality jobs and decline in health outcomes. Conclusion Extended working lives mean that people will be 'exposed' to work for longer, and this exposure will occur at a life stage characterised by declining health for many. Our findings show that ensuring older workers have access to secure jobs which allow for control over work time, skill use and fair rewards will be essential if policy goals to boost participation and productivity, as well as reduce the health and care costs of the elderly, are to be met.